Development of Green Bonds in Indonesia - Mutia Wahyuningsih; Utami, Wiwik; Endri, Endri; Kurniasih, Augustina (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose –This paper explains the development of Green Bonds in Indonesia by providing information regarding the characteristics of green bonds and macroeconomics during the 2018 – 2023 period.Methodology/approach –Research that provides information regarding the characteristics of green bonds and macroeconomics by collecting data on 29 green bonds issued in the 2018 - 2023 period. Findings –It was found that from the results of descriptive statistics the research variables in the form of Maturity, Rating, Coupon, BI Rate, Inflation and Exchange Rate can explain the development of Green Bonds in Indonesia from the 2018 - 2023 period.Novelty/value –Because green bonds were only issued in 2018, it is very important to understand the development of Green Bonds in Indonesia by looking at the characteristic variables of green bonds along with macroeconomic variables on the first date of green bond issuance.